Lateral Femoral Condyle CRATER sign of BRIK an Ancillary Sign of Lateral Patellar Dislocation - Iyengar, Karthikeyan P.; Bhamidipaty, Kanaka Durga Prasad; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2022)
Introduction Acute lateral patellar dislocation is a common knee injury pattern. However, coincidental osseous defect may be present in normal knees.Purpose Evaluate the characteristics of osseous bone defect and describe a new ancillary sign associated with lateral patellar dislocation.Materials and Methods Magnetic resonance imaging (MRI) of 50 consecutive patients referred following a traumatic lateral patellar dislocation of the knee joint and 50 patients with knee pain without MR features of patellar dislocation were obtained for evaluation over a 7-year period. They were analyzed for location of bony defects in the periarticular region.Results Of the 50 patients who underwent MRI following a reduced traumatic lateral patellar dislocation, 3 patients had an osseous “crater” of more than 2 mm in depth on the non-articular surface of the lateral femoral condyle. None of control group of patients had an osseous defect measuring more than 2 mm in depth.Conclusion This associated finding of an osseous “crater” of more than 2 mm on the non-articular surface of the lateral femoral condyle following traumatic lateral patellar dislocation is a rare occurrence. We highlight this as an ancillary sign of lateral patellar dislocation necessitating careful evaluation (Crater sign of Bhamidipaty Rajesh Iyengar Kartik [BRIK]). The presence of lateral femoral condyle “CRATER” sign of BRIK on MRI undertaken for other reasons in the knee, in the absence of osseous edema may suggest a past episode of severe, reduced patellar dislocation.
Keywords: knee joint; knee injuries; patellar dislocation; radiology; magnetic resonance imaging